Modelling heat and mass transfer in solar evaporation systems. (December 2021) - Fillet, R.; Nicolas, V.; Fierro, V.; Celzard, A.
Highlights: A 2D asymmetric model has been developed to simulate water evaporation systems. The impact of boundary conditions on the evaporation rate has been demonstrated. A high evaporation surface allows the evaporation rate to be substantially increased. Geometric optima for maximising evaporation have been identified. Abstract: A two-dimensional axisymmetric model of a solar evaporator was developed, based on a rigid biosourced open-cell foam floating on the surface of water contained in a beaker, including a set of boundary conditions and water transport in the porous medium. Experiments were carried out to validate the model for two cases, with and without a layer of insulating material around the beaker. Several concrete cases of experimental solar evaporation studies recently reported in the literature, with or without insulation, radiation intensification, etc., have then been studied in the light of our model. We have thus been able to compare the observed trends with those of the numerical model in order to explain the results reported in the literature and, in some cases, to find a geometric optimum. The effect of ambient conditions on the evaporation rate was investigated, and significant changes were observed by modifying solar input, air temperature and air humidity. We also showed that increasing the evaporation area and using an insulating layer between the water and the evaporative material increases the evaporation performance.